Community functional trait composition at the continental scale: the effects of non‐ecological processes. Issue 5 (3rd June 2016) - Lawing, A. Michelle; Eronen, Jussi T.; Blois, Jessica L.; Graham, Catherine H.; Polly, P. David
Abstract : Ecological communities and their response to environmental gradients are increasingly being described by measures of trait composition at the community level – the trait‐based approach. Whether ecological or non‐ecological processes influence trait composition between communities has been debated. Understanding the processes that influence trait composition is important for reconstructing paleoenvironmental conditions from fossil deposits and for understanding changes in community functionality through time. Here, we assess the influence of ecological and non‐ecological processes on the distribution of traits within North American mammals. We found that non‐ecological processes including historical contingency, spatial autocorrelation, and evolutionary history do not influence trait composition; however, the variance in trait composition is highly explained by climate gradients. Our results suggest that habitat breadth, terrestriality, diet breadth, and reproductive traits are strong candidates as proxies for measuring functional aspects of environments in the past and present.